2007
DOI: 10.1111/j.1751-7893.2007.00044.x
|View full text |Cite
|
Sign up to set email alerts
|

What are the effects of providing evidence‐based information on eating disorders and their treatments? A randomized controlled trial in a symptomatic community sample

Abstract: A brief community-based intervention aimed to improve knowledge and beliefs about EDs and their treatments may be a valuable first step in improving health-related outcomes for people with ED, but more research is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 29 publications
2
20
0
2
Order By: Relevance
“…Participants were most likely to identify the problem for the women with BN as one of low self-esteem and had modest or low regard for evidence based or specialist therapies compared to non-specialists. As we found previously (Hay et al, 2007a) a BN-MHL intervention had no significant impact on changing attitudes or improving symptoms and in this study it also had no significant impact on improving mental health related quality of life. The findings indicated that merely providing people with information about treatments for bulimic EDs and also advising them to seek help did not result in notable changes in behaviour or beliefs.…”
Section: Summary and Introduction To Trial Of Self-help Approachessupporting
confidence: 77%
See 1 more Smart Citation
“…Participants were most likely to identify the problem for the women with BN as one of low self-esteem and had modest or low regard for evidence based or specialist therapies compared to non-specialists. As we found previously (Hay et al, 2007a) a BN-MHL intervention had no significant impact on changing attitudes or improving symptoms and in this study it also had no significant impact on improving mental health related quality of life. The findings indicated that merely providing people with information about treatments for bulimic EDs and also advising them to seek help did not result in notable changes in behaviour or beliefs.…”
Section: Summary and Introduction To Trial Of Self-help Approachessupporting
confidence: 77%
“…In the area of eating disorders we have conducted a small randomized controlled study of a brief postal mental health literacy intervention in community women with bulimic eating disorders. At the end of a year symptomatic improvement, less pessimism about how difficult eating disorders are to treat, improved recognition and knowledge, as well as increased help-seeking were observed in both groups (Hay et al, 2007a). Those randomized to receive the mental health literacy intervention also had improved mental health related quality of life.…”
Section: Introductionmentioning
confidence: 93%
“…Note: The present paper is focussed on the 2-year follow-up and 6-month and 1-year follow-up data are presented elsewhere in e.g. Hay et al (2007) and …”
Section: Appendixmentioning
confidence: 99%
“…Compared to controls, at 1 year (the end of the RCT) those in the intervention group had improved mental health related quality of life. Symptomatic improvement, less pessimism about how difficult eating disorders are to treat, improved recognition and knowledge, as well as increased help-seeking were observed in both groups (Hay, Mond, Darby, Rodgers, & Owen, 2007).…”
mentioning
confidence: 93%
“…Some of many modalities and therapies used include nutritional supplementation, cognitive behavioural therapy (CBT), medication, family counselling, dietary advice, counselling and/or health monitoring among others [6]. Individuals with an ED are known to seek help from complementary and alternative therapies (CAM) [12].…”
Section: Introductionmentioning
confidence: 99%